Skeletal maturation of the cervical vertebrae: association with various types of malocclusion - Mônica Costa Armond; Rodrigo Generoso; Saulo Gabriel Moreira Falci; Maria Letícia Ramos-Jorge; Leandro Silva Marques (Sociedade Brasileira de Pesquisa Odontológica, 2012)
The identification of the skeletal maturation stage of the cervical vertebrae has proven an important reference for orthodontic diagnosis. The aim of the present study was to determine the association between the skeletal maturation stage of the cervical vertebrae and types of malocclusion according to the age and gender of participants. A total of 361 individuals (168 males and 193 females) between 8 and 14 years of age were selected from a convenience sample. Malocclusions were diagnosed through study models using the Angle classification. Maturation stages of the cervical vertebrae were determined using the method proposed by Hassel and Farman. Statistical analysis involved the chi-square test (p £ 0.05) and multiple logistic regression (forward stepwise procedure). Significant differences were observed between the stage of skeletal maturation of the cervical vertebrae and gender at ages 11, 12 and 14 years. Males with Class II malocclusion were twice as likely to be in Stage 1 or 2 of cervical vertebra maturation than individuals with Class I malocclusion (OR = 2.1 [CI 95%, 1.33-3.18]). There were no differences between individuals with Class I and Class III malocclusions. The association between skeletal maturation of the cervical vertebrae and type of malocclusion was significant, suggesting a skeletal component in the determination of Class II malocclusions.